Pengajaran Bahasa Arab Dengan Pendekatan Behavioristik - Akla Akla (Institut Agama Islam Negeri (IAIN) Metro, 2021)
This study implicitly describes the participatory learning process of Arabic with a behavioristic approach. The research questions formulated are (1) how does the use of a behavioristic approach take place in the Arabic language learning process? (2) how the students' motivation before and after the use of a behavioristic approach; and (3) how effective is the use of a behavioristic approach in improving Arabic learning outcomes. This study uses a combined research approach to test learning competencies and the learning process. Respondents of the study were students of class V and VI Madrasah Ibtidaiyah Al Imam Lampung Timur totaling 35 students. The instruments used in this study were interviews, questionnaires, and tests. The results showed that the use of a behavioristic approach that was oriented towards providing stimulus-response continuously improved students' language acquisition. This acquisition is in the form of increased mastery of vocabulary, speaking, reading, and writing. A behavioristic approach to learning can improve Arabic learning outcomes. In addition to improving learning outcomes, a behavioristic approach can increase learning motivation. The increase in learning outcomes and learning motivation can be predicted because the behavioristic approach uses a pattern of repeated stimulus that is designed in a pleasant environment.